Effect of Configuration of Protective Fabrics on Thermal Protective Performance under Steam Exposure (Journal of Fiber Bioengineering and Informatics, 2018)
A novel steam simulator was employed in this study to evaluate thermal protective performance of protective clothing while exposing to steam hazard. Single- and double-layer fabric systems were selected, and different configurations of moisture barrier were exposed to steam hazard for investigating the effect of configuration of protective fabrics on the thermal protective performance. The skin bio-heat transfer and Henriques burn integral models were used to predict the required times to reach 2nd and 3rd degree skin burn. The results demonstrated that the thermal protective performance of protective clothing under steam exposure was determined by the air permeability, the thickness, the mass, and the surface properties of fabric. Even though the moisture barrier provided excellent protective performance for steam exposure, the configuration of moisture barrier presented a decisive influence on the role of moisture barrier. The findings obtained in this study provide technical data for the performance improvement of protective clothing under steam hazard.
Keywords: Thermal Protective Performance; Steam Exposure; Protective Fabric; Configuration.